2012
DOI: 10.1210/jc.2011-2178
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of a Combined Cytotoxic Thyroglobulin and Thyroperoxidase Epitope-Specific Cellular Immunity in Hashimoto's Thyroiditis

Abstract: We here report for the first time that both antigens, TPO and Tg, are recognized by CD8-positive T cells and are involved in the thyroid destruction process leading to clinical disease manifestation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
1
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 24 publications
4
46
1
2
Order By: Relevance
“…Although it was suggested that HT may mainly result from local autoimmune mechanisms in the thyroid gland [12,13], changes in the peripheral T cell distribution were detected in our study. Our results demonstrated a significant increase of CD28-negative T cells in HT patients, associated with CMV-seropositivity within the CD8+ T cell subpopulation.…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…Although it was suggested that HT may mainly result from local autoimmune mechanisms in the thyroid gland [12,13], changes in the peripheral T cell distribution were detected in our study. Our results demonstrated a significant increase of CD28-negative T cells in HT patients, associated with CMV-seropositivity within the CD8+ T cell subpopulation.…”
Section: Discussioncontrasting
confidence: 77%
“…Hashimoto’s thyroiditis (HT) is an organ-specific autoimmune disorder of the thyroid gland associated with diffuse lymphoid infiltration, inflammatory destruction of follicular cells and auto-antibodies against thyroid-specific self-antigens [10-12]. However, the etiopathogenesis of HT is far from being clearly understood [13].…”
Section: Introductionmentioning
confidence: 99%
“…[58] In the same study Hashimoto's thyroiditis patients showed significantly lower proportions of CD8+ T cells than healthy control. [58] Some authors have demonstrated a significant decrease in all populations of T-lymphocytes in Graves’ disease hyperthyroid patients. [55] These reports are contradictory to our finding of increased peripheral total lymphocytic count in AITDs.…”
Section: Discussionmentioning
confidence: 94%
“…16,24 Moving from these experiments in mice, the group of Schott recently studied TPO-and Tg epitope- this study supports the view that in HT a combined TPOand T-specific cytotoxic immnune response does occur. 25 In the last few years, evidence was also accumulated supporting the concept that INF-γ inducible chemokines, such as CXCL10, play an important role in the initial stages of thyroid autoimmunity. When stimulated by IFN-γ, thyroid follicular cells secrete CXCL10, which in turn recruits into the thyroid Th1 lymphocytes expressing CXCR3 and secreting IFN-γ, thus establishing a loop which reinforces and maintains the autoimmunity process.…”
Section: Basic Mechanisms In the Development Of Thyroid Autoimmunitymentioning
confidence: 99%